Virtual regional dialogue on options to promote more inclusive weather index insurance - Surie, Mandakini D.; Aheeyar, Mohamed M. M.; de Silva, Sanjiv; Raut, Manita (2021)
Over the past decade, countries in South Asia have experienced more frequent and intense extreme weather events – floods and droughts – driven by climate change. In 2021 alone, Bangladesh, India, and Nepal experienced intense monsoon rainfall and floods spurred by an erratic monsoon, even as parts of India and Pakistan experienced intense heatwaves and drought The Intergovernmental Panel on Climate Change’s (IPCC) latest report released in August 2021, suggests that such events are only likely to increase, noting that at 1.5 degrees and 2 degrees Celsius global warming levels, mean precipitation and monsoon extremes are projected to intensify in summer over India and South Asia.